Pengaruh Transparansi, Kejelasan Sasaran Anggaran, Pemanfaatan Teknologi Informasi, dan Kepatuhan Undang-Undang terhadap Akuntabilitas Pengelolaan Dana Desa - Ulfi Nella Audia; Erly Mulyani (Universitas Negeri Padang, 2023)
This study aims to determine transparency, targets, budgets, utilization of information technology, and compliance with accountability laws on village fund management (Empirical Study in Nagari, Padang Pariaman Regency). The population used in this study were 103 nagari in Padang Pariaman Regency which opened 824 nagari devices. The sampling technique used purposive sampling method. In determining the number of samples, Isaac and Michael use the formula so that 262 nagari devices can be obtained. This type of research is quantitative research. The source of data in this study is primary data by distributing questionnaires to village officials in Padang Pariaman Regency. Data analysis used multiple linear regression analysis. The results of this study indicate that transparency, application of information technology, and legal compliance have a positive and significant impact on the accountability of village fund management. While the budget target does not affect the accountability of village fund management.